2014
DOI: 10.1021/jp506999k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Morphology on the Dielectric Properties of Porous Carbons for Microwave Absorption Applications

Abstract: The porous carbons (PCs) with tunable morphologies and pore sizes were prepared by the sol–gel process via a freeze-drying technique for microwave absorption applications. The results of Raman spectroscopy and nitrogen sorption analysis showed that the graphitization degree was barely influenced as the ratio of tert-butanol (T) to resorcinol (R) decreased, while the pore morphologies changed from the disordered slit-shaped pores to the uniform cage-like pores. Dielectric properties of the as-prepared carbon sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 38 publications
1
56
1
Order By: Relevance
“…The presence of two types of nitrogen elements was consistent with the structure of Cu-SOCBP. The binding energies of pyridinic-N found in this study were higher than those usually reported for pyridinic-N, and this is an apparent indication of complexation between copper ions and The surface areas and pore volumes of the samples including Vulcan XC-72 carbon and Cu-SOCBP/C were determined by nitrogen sorption analysis [28]. The sorption isotherms of samples are shown in Figure 2.…”
Section: Xps and Powder X-ray Diffraction Of The Catalystcontrasting
confidence: 46%
See 1 more Smart Citation
“…The presence of two types of nitrogen elements was consistent with the structure of Cu-SOCBP. The binding energies of pyridinic-N found in this study were higher than those usually reported for pyridinic-N, and this is an apparent indication of complexation between copper ions and The surface areas and pore volumes of the samples including Vulcan XC-72 carbon and Cu-SOCBP/C were determined by nitrogen sorption analysis [28]. The sorption isotherms of samples are shown in Figure 2.…”
Section: Xps and Powder X-ray Diffraction Of The Catalystcontrasting
confidence: 46%
“…This favorable structure may play a pivotal function in improving the ORR activity of materials. The surface areas and pore volumes of the samples including Vulcan XC-72 carbon and Cu-SOCBP/C were determined by nitrogen sorption analysis [28]. The sorption isotherms of samples are shown in Figure 2.…”
Section: Xps and Powder X-ray Diffraction Of The Catalystmentioning
confidence: 99%
“…Structural properties, chemical functionality as well as particle size distribution (PSD) are some special intrinsic characteristics having the dominant effect on the electromagnetic properties of these types of absorbents. 4,8,[18][19][20][21] For example, Huang et al 22 investigated the effect of pore texture of sol-gel derived resorcinol-furfural on EM characteristics of the mesoporous carbons. It was concluded that the synthesized porous carbons with a cage-like structure exhibited interesting electromagnetic properties in terms of the real and imaginary parts of the permittivity.…”
Section: 7-13mentioning
confidence: 99%
“…The two broad peaks positioned at 2q ¼ 24 and 42 correspond to the reections of (002) and (100) planes of graphite, respectively. 22,29,35 Since the peak intensity of d 002 plane in CAs is weak, it is concluded that the CAs structure consists of low degree of crystallinity.…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation